Locating shelters and telecom-relief centers considering uncertainty in the disaster time (Case study: flood disaster in region #3 of Tehran) - Ahmad Mohammadi; Saied Yaghoubi; Jamal Nahofti Kohne; Mirsaman Pishvaie (مدیریت صنعتی, 2015)
The most important issues that should be considered in studying disaster management include temporary settlement of injured population, supplying relief commodities, designing an appropriate communication infrastructure for communication during disaster. For this purpose, in this paper a model has been proposed for locating shelters, warehouses of relief commodities, and also telecom towers, whereas warehouses of relief‌ commodities and telecom towers have been considered as the telecom-relief center for reducing costs and improving services. The problem has been modeled as a nonlinear and bi-objective model, while for solving the problem normalization method and linearization approach have been applied. With respect to significance of unstable conditions and dynamic environment in natural disasters, the model has been considered under uncertainty and possibilistic programming approach is used to cope with this issue. The proposed model is implemented in the flood disaster case study of Tehran and the obtained results show that the optimal location of the facility can help the decision makers of disaster management in this area to increase service provision during disaster.